2018
DOI: 10.1186/s12905-018-0640-y
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of knowledge, attitudes, and beliefs related to tobacco use and secondhand smoke among women in Aleta Wondo, Ethiopia

Abstract: BackgroundBy 2030, the Sub-Saharan African region is projected to be the epicenter of the tobacco epidemic. While smoking prevalence is currently low among women (< 2%), the prevalence among men (7.7% overall and up to 27% depending on region) makes exposure to secondhand smoke a pressing concern for women and children. To prevent the uptake of smoking among women and address tobacco-related risks, including secondhand smoke exposure, a greater understanding of women’s related perceptions is needed. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Unless strong periodic monitoring of tobacco smoking, evaluation of tobacco control intervention and sustained vigilance on tobacco industry interventions are implemented, the impact of tobacco use will continue to claim the lives of thousands. The level of public awareness regarding regulations and prohibitions of tobacco use and its devastating health consequences remain very low in Ethiopia (24,43). This finding agrees with lessons from other countries in Africa and around the world (44,45).…”
Section: Evaluation: Tobacco Prevention and Controlsupporting
confidence: 72%
See 1 more Smart Citation
“…Unless strong periodic monitoring of tobacco smoking, evaluation of tobacco control intervention and sustained vigilance on tobacco industry interventions are implemented, the impact of tobacco use will continue to claim the lives of thousands. The level of public awareness regarding regulations and prohibitions of tobacco use and its devastating health consequences remain very low in Ethiopia (24,43). This finding agrees with lessons from other countries in Africa and around the world (44,45).…”
Section: Evaluation: Tobacco Prevention and Controlsupporting
confidence: 72%
“…The level of public awareness regarding regulations and prohibitions of tobacco use and its devastating health consequences remain very low in Ethiopia ( 24 , 43 ). This finding agrees with lessons from other countries in Africa and around the world ( 44 , 45 ).…”
Section: Processmentioning
confidence: 99%
“…Prev. Cessation 2020;6(May):32 https://doi.org/10.18332/tpc/120940 associated with tobacco use and SHS exposure was limited 16 . Another study among school children and community adults in four cities in China, India, Mexico and England showed that the specific health effects of tobacco use and SHS exposure were poorly understood 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Children are even more vulnerable to the toxicity of SHS as their body is still developing 7 , 10 , 11 . There is also well-established evidence that exposure to SHS by pregnant women is associated with low birthweight 6 , 12 , risk of cot death 6 , 13 , middle ear infection 6 , 14 , 15 and exposure of children to lower tract respiratory infections 6 , 14 , 16 , 17 . A recent study among women in Ethiopia showed that respondents’ knowledge on the specific health risks associated with tobacco use and SHS exposure was limited 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation